The Abbott RealTime High Risk HPV test is a clinically validated human papillomavirus assay for triage in the referral population and use in primary cervical cancer screening in women 30 years and older - Poljak, Mario (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2013)
Introduction: Human papillomavirus (HPV) testing has become an essential part of current clinical practice in the management of cervical cancer and precancerous lesions. We reviewed the most important validation studies of a next-generation real-time polymerase chain reactionbased assay, the RealTime High Risk HPV test (RealTime)(Abbott Molecular, Des Plaines, IL, USA), for triage in referral population settings and for use in primary cervical cancer screening in women 30 years and older published in peer-reviewed journals from 2009 to 2013. RealTime is designed to detect 14 high-risk HPV genotypes with concurrent distinction of HPV-16 and HPV-18 from 12 other HPV genotypes. The test was launched on the European market in January 2009 and is currently used in many laboratories worldwide for routine detection of HPV. Methods: We concisely reviewed validation studies of a next-generation real-time polymerase chain reaction (PCR)based assay: the Abbott RealTime High Risk HPV test. Results: Eight validation studies of RealTime in referral settings showed its consistently high absolute clinical sensitivity for both CIN2+ (range 88.3100%) and CIN3+ (range 93.0100%), as well as comparative clinical sensitivity relative to the currently most widely used HPV test: the Qiagen/Digene Hybrid Capture 2 HPV DNA Test (HC2). Due to the significantly different composition of the referral populations, RealTime absolute clinical specificity for CIN2+ and CIN3+ varied greatly across studies, but was comparable relative to HC2. Four validation studies of RealTime performance in cervical cancer screening settings showed its consistently high absolute clinical sensitivity for both CIN2+ and CIN3+, as well as comparative clinical sensitivity and specificity relative to HC2 and GP5+/6+ PCR. Conclusion: RealTime has been extensively evaluated in the last 4 years. RealTime can be considered clinically validated for triage in referral population settings and for use in primary cervical cancer screening in women 30 years and older.
Keywords: cervical cancer; human papillomavirus testing; validation studies